The faceless terrorist: a study of critical events in Tajikistan - Roche, Sophie (Transcultural Research – Heidelberg Studies on Asia and Europe in a Global Context, 2019)
Chapter 1. Introduction -- Chapter 2. Ethnographers, Functionaries, Mullahs, and the Making of “Muslims” -- Chapter 3. Biographical Narratives of Muslim Activists -- Chapter 4. Islamizdat Literature on the Notions of Jihad, Shahid, Mujahid, and Death -- Chapter 5. A Conflict Goes Online -- Chapter 6. Critical Events -- Chapter 7. The Politics of Traditions -- Chapter 8. A Cousin, a Mujahid, a Terrorist -- Chapter 9. Relation as Operations of Experiences